The use of calcitonin in the effective preoperative management of neonatal hypercalcemia in congenital mesoblastic nephroma - Galvez, Cinthia S.; Rifai, Kareem; Chheda, Sadhana; Zerah, Michele (International Journal of Contemporary Pediatrics, 2025)
Subcutaneous administration of calcitonin is effective in the preoperative management of hypercalcemia associated with congenital mesoblastic nephroma (CMN). The short onset of action (within 2 hours) and duration (6 to 8 hours), makes it a viable alternative to bisphosphonates (action 48 hours and duration of 7 to 14 days). A 15-day-old late preterm, male, presented with dehydration, failure to thrive and a large abdominal mass. On admission, he was hypertensive, and a firm mass was palpable in the abdomen. Severe hypercalcemia was noted on the blood work. An abdominal ultrasound shows a large 9×8 cm dominant solid right renal mass. Echo and electrocardiography (ECG or EKG) were normal. The patient initially received IV hydration, nicardipine and furosemide. The hypercalcemia persisted after 24 hours of treatment; thus, one dose of calcitonin (6 units/kg subcutaneously) was given, resulting in a decrease in serum calcium to the upper limits of normal within 4 hours. The patient then underwent a successful radical right uretero-nephrectomy. Pathology reported congenital mesoblastic nephroma (CMN) of the cellular type. This is the third case report describing the use of calcitonin for a likely PTH-rP-mediated severe hypercalcemia in a neonate with CMN.